Modelling digital capability as a game changer to enhance SME’s performance - Mohammad Fakhruddin Mudzakkir; Wahyu Eko Pujianto; Al-Baraa Abdulrahman Al-Mekhlafi; Dahlia Fernandez; Ajeng Dyah Paraswati (Universitas Negeri Surabaya, Indonesia, 2026)
Digital technology can help industries face competition, particularly play a vital role in improving SMEs' performance. This study aims to investigate the relationship between digital leadership and SMEs' performance by examining digital capabilities, with a focus on the crucial roles of digital and innovation capabilities as mediators and entrepreneur orientation as a moderator. A survey technique was employed to identify Small and Medium Enterprises (SMEs) in East Java. A total of 205 responses were collected and designed using Likert scale and the data were analysed using PLS-SEM. The results indicate that digital leadership influences digital capability, which in turn influences SMEs performance. Additionally, innovation capability influences both digital leadership and SMEs performance. In addition, entrepreneur orientation cannot moderate the relationship between innovation capability and SMEs performance. However, entrepreneur orientation is able to mediate the relationship between digital capability and SMEs performance. This study considers among first studies addressing these critical relationships in this sector. Therefore, this study determines how leaders determine the ways to achieve improved SMEs performance. Ultimately, this study provides evidence of the importance of digital and innovation capabilities for competitiveness.